The shifting shape and functional specializations of the cell cycle during lineage development. Issue 2 (11th September 2020) - Hwang, Yung; Hidalgo, Daniel; Socolovsky, Merav
Abstract: Essentially all cell cycling in multicellular organisms in vivo takes place in the context of lineage differentiation. This notwithstanding, the regulation of the cell cycle is often assumed to be generic, independent of tissue or developmental stage. Here we review developmental‐stage‐specific cell cycle adaptations that may influence developmental decisions, in mammalian erythropoiesis and in other lineages. The length of the cell cycle influences the balance between self‐renewal and differentiation in multiple tissues, and may determine lineage fate. Shorter cycles contribute to the efficiency of reprogramming somatic cells into induced pluripotency stem cells and help maintain the pluripotent state. While the plasticity of G1 length is well established, the speed of S phase is emerging as a novel regulated parameter that may influence cell fate transitions in the erythroid lineage, in neural tissue and in embryonic stem cells. A slow S phase may stabilize the self‐renewal state, whereas S phase shortening may favor a cell fate change. In the erythroid lineage, functional approaches and single‐cell RNA‐sequencing show that a key transcriptional switch, at the transition from self‐renewal to differentiation, is synchronized with and dependent on S phase. This specific S phase is shorter, as a result of a genome‐wide increase in the speed of replication forks. Furthermore, there is progressive shortening in G1 in the period preceding this switch. Together these studies suggest an integrated regulatory landscape of the cycle and differentiation programs, where cell cycle adaptations are controlled by, and in turn feed back on, the propagation of developmental trajectories. This article is categorized under: Congenital Diseases > Stem Cells and Development Abstract : Cell cycle speed and dynamics determine developmental state and cell fate.